(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Danylyuk S. S. Formation of Modern Specialists’ Professional Competence in the Process of Conducting of Videoconferences. The paper deals with the highlighting of the formation of modern specialists’ professional competence in the aspect of the usage of such Internet technology as videoconference in the educational process. Furthermore, the benefits of using videoconferencing in the educational process are defined. Attention is also focused on basic directions of the preparatory work aimed at conducting videoconferences.